Some Results on Asymptotic Stability of Order α - Vu Thi Thu Huong; Vu Tuan (Український математичний журнал, 2005)
Quasi-equiasymptotic stability of order α (α ∊ R₊*) with respect to a part of variables is considered. Some sufficient conditions, a converse theorem, and a theorem on multistability are proved.